Komunikasi Persuasif Majelis Tabligh Pimpinan Cabang Muhammadiyah Terbanggi Besar dalam Meningkatkan Kemampuan Public Speaking Muballigh - Hariyanto, Hariyanto; Muhammad Irhamdi; Bagus Darmawan (Program Studi Komunikasi dan Penyiaran Islam, 2024)
Persuasive communication is the delivery of messages with the aim of influencing others through psychological aspects without any coercion. This study aims to explain the implementation of persuasive communication of the Terbanggi Besar PCM Tabligh Council in improving the ability of public dissemination of muballigh. This research is a field research through a descriptive method using observation, interview, and documentation tools. The results of the study show that Majlis Tabligh PCM Terbanggi Besar applies persuasive communication in its principles AIDDA yakni Attention, Inters / Desire, Decision, Action and provide space for two-way communication.